Improving access to pulmonary rehabilitation for patients with COPD treated for substance misuse in the London Borough of Islington - Duncan Stewart; Jane Simpson; Divya Narasimhan (BMJ Open Quality)
Chronic obstructive pulmonary disease (COPD) is a collection of conditions that cause permanent damage to the lungs. Among a range of treatment options, patients can benefit from pulmonary rehabilitation (PR) programmes involving physical exercises and education.The risk of developing COPD is higher for substance misusers than the general population. Substance misusers with COPD have more severe symptoms and poorer health outcomes than other COPD patients, and experience inequalities in accessing PR services.This project aimed to work with a local substance misuse service to increase the referrals of patients with COPD with a history of drug and/or alcohol problems to a PR programme in the London Borough of Islington. Quality improvement methods were used to explore barriers to accessing PR and to identify ways of making referral to PR easier. A series of change ideas were implemented and tested sequentially through plan–do–study–act, including updating referral systems, educating staff and improving access to diagnosis.The primary objective was to achieve 100 eligible referrals during the 14-month project period. In practice, a total of 57 patients were referred to the programme. Sustained engagement with patients was challenging, with significant attrition observed from referral to programme completion. However, there was indicative evidence of clinical improvements in dyspnoea and exercise capacity among PR completers and qualitative feedback of improved health and well-being.Although referrals numbers were less than expected, we have established an innovative respiratory care pathway for substance misusers, founded on a holistic approach to diagnosis and treatment. There are also clear pointers as to how this approach can be sustained and developed further to maximise the benefits for this cohort of patients.